The Relationship between Parenting and Personality of Teenagers in Cibalugung Village - Rohman, Abdur; Hamdani, Nessa; Kosala, Andri (International Journal Labs, 2022)
The biggest factor that shapes a child's personality is the family environment, especially the attitude of parents. Parents' attitudes, behaviors, and habits are always seen, judged, and imitated by children and then become habits for their children. Whatever stimulus is received has a great impact on child development because from the stimulus received, the child's brain will unconsciously manage and store it so that it becomes a science. This study aims to obtain data and information on how parenting affects the formation of teenagers’ personalities in Cibalagung Village RT. 003 RW. 004 Kel. Pasirjaya Bogor City. The method used in this study is a quantitative descriptive method. As for the techniques used in data collection in this study, namely questionnaires, observations, and literature studies. The population in this study is teenagers in Cibalagung RT 03 RW 04 Pasirjaya Village, Bogor City, which amounts to 35 people. The sample in this study is teenagers. The number of sample members in this study is 35 people. The value of rcount 0.61 after being consulted with the interpretation table then the r-value is at an interval of 0.60 – 0.799 with the “Strong” category. This shows that parenting plays a strong role in the personality of teenagers in Cibalagung RT 03 RW 04 Pasirjaya Village.